Zirconia phase transformation in retrieved, wear simulated, and artificially aged ceramic femoral heads. Issue 12 (20th June 2017) - Parkes, Maria; Sayer, Kathryn; Goldhofer, Markus; Cann, Philippa; Walter, William L.; Jeffers, Jonathan
ABSTRACT: Zirconia in Zirconia toughened alumina ceramic hip replacements exists in an unstable state and can transform in response to stress giving the material improved fracture toughness. Phase transformation also occurs under hydrothermal conditions such as exist in vivo. To predict the hydrothermal aging that will occur in vivo accelerated aging procedures have been used, but validation of these models requires the study of retrieved hip joints. Here 26 retrievals are analysed to determine the degree of phase transformation in vivo. These were compared with virgin heads, heads that had undergone the accelerated aging process and heads wear tested to 5 million cycles in a hip simulator. Monoclinic content and surface roughness were measured using Raman spectroscopy and white light interferometry respectively. The monoclinic content for retrieved heads was 28.5% ± 7.8, greater than twice that in virgin, aged, or wear tested heads and did not have a significant correlation with time, contrary to the predictions of the hydrothermal aging model. The surface roughness for retrieved heads in the unworn area was not significantly different to that in virgin, aged, or unworn areas of wear tested heads. However in worn areas of the retrieved heads, the surface roughness was higher than observed in wear simulator testing. These results indicate that current testing methodologies do not fully capture the operational conditions of the material and the real performance of future new materials may not be adequately predicted by current pre‐clinical testing methods. © 2017 The Authors. Journal of Orthopaedic Research Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society 35:2781–2789, 2017.